Prevalence, characteristics and outcome of cardiac manifestations in critically-ill antiphospholipid syndrome patients. Issue 133 (December 2022) - Azoulay, Lévi-Dan; Pineton de Chambrun, Marc; Larcher, Romaric; Pène, Frédéric; Argaud, Laurent; Mayaux, Julien; Jamme, Matthieu; Coudroy, Remi; Mathian, Alexis; Gibelin, Aude; Azoulay, Elie; Tandjaoui-Lambiotte, Yacine; et al.
Abstract: Aims: Antiphospholipid syndrome (APS) is a rare autoimmune disease defined by thrombotic events occurring in patients with persistent antiphospholipid antibodies. Cardiac manifestations in critically-ill APS patients are poorly investigated. We conducted a study to assess the prevalence, the characteristics and the prognosis of cardiac manifestations in thrombotic APS patients admitted to intensive care unit (ICU). Methods and results: A French, national, multicentre, retrospective study, conducted, from January 2000 to September 2018, including all APS patients admitted to 24 participating centres' ICUs with any new thrombotic (arterial, venous or microvascular) manifestation. Cardiac manifestations were defined as any new cardiac abnormalities relying on clinical examination, cardiac biomarkers, echocardiography, cardiac magnetic resonance (CMR) and coronarography. One hundred and thirty-six patients (female 72%) were included. Mean age at ICU admission was 46 ± 15years. Cardiac manifestations were present in 71 patients (53%). In patients with cardiac involvement, median left ventricular ejection fraction (LVEF) was 40% [28–55], troponin was elevated in 93% patients, coronary angiogram (n = 19, 27%) disclosing a coronary obstruction in 21%. CMR (n = 21) was abnormal in all cases, with late gadolinium enhancement in 62% of cases. Cardiac manifestations were associated with a non-significant increase of mortality (32% vs. 19%, p = 0.08). After 1-year follow-up, median LVEF was 57% [44–60] in patients with cardiac involvement. Conclusion: Cardiac involvement is frequent in critically-ill thrombotic APS patients and may be associated to more severe outcome. Increased awareness on this rare cause of myocardial infarction with or without obstructive coronary artery is urgently needed. Graphical abstract: Image 1 Highlights: Cardiac manifestations occurs in 53% critically-ill thrombotic APS patients. Half patients with cardiac involvement have proven or suspected MINOCAs. Patients with cardiac involvement tend to have a worse outcome.